Curricular innovation in higher education: experiences lived by teachers in a school of nursing - Guerra-Guerrero, Verónica; Miño-González, Carmen Gloria; Poblete-Troncoso, Margarita; Cofré-González, Carmen Gloria; Ceballos-Vásquez, Paula; Jara-Rojas, Ana (Universidad y Salud, 2018)
Introduction: In recent decades, in Chile, vocational training in nursing has undergone transformations in their study plans, moving from having a traditional curriculum to one based on competencies, in accordance with the current demands of the labor market. Objective: To analyze two topics derived from the study focused on understanding the life experiences of teachers in a Nursing School on the curricular innovation. Materials and methods: A phenomenological study through in-depth interviews was conducted to twenty teachers, who have participated in the training of nurses. Sampling for convenience was done according to the data saturation criterion. The data analysis was thematic type as proposed by Van Manen. The research was approved by the Ethics Committee of the institution. Results: Seven main themes were identified, two of which are analyzed in this article: innovation as a complex process and unchanged changes. Conclusions: The transition from a traditional curriculum to one based on competences, from the experience of teachers, implies complex challenges and profound changes; considering this, higher education institutions have to provide the conditions to facilitate such a process.